The Effect of Structural Transformation, Population, Labor Force Participation Rate, and Human Development Index Among Inequality in Kedungsepur Area in 2010-2019 - Nurindra Cahyani; Mulyo Hendarto Robertus (Diponegoro Journal of Economics, 2022)
A faster development of secondary and tertiary sectors than primary sector indicates a structural transformation in KEDUNGSEPUR area. However, the diversity characteristic across regions in KEDUNGSEPUR area can causes inter-regions inequality. This study aims to determine the effect of structural transformation, population, labor force participation rate, and human development index among inequality in KEDUNGSEPUR area in 2010-2019. Analysis data on this study using panel data regression analysis with a fixed effect model. Result shows that the population variable significantly affects inequality in KEDUNGSEPUR area, while the structural transformation, labor force participation rate and human development index do not affect inequality in KEDUNGSEPUR area. However, the variables of structural transformation, population size, labor force participation rate and the human development index equally affect inequality in KEDUNGSEPUR area.